Speech Treatment for People with Cerebellar Multiple System Atrophy (MSA-C): A Pilot Randomised Controlled Trial of Two Approaches - Anja Lowit; Kaiyue Xing; D. Priya Shanmugarajah; Emma Foster; Suzanna Duty; David Young; Jan Stanier; Christopher Kobylecki; Marios Hadjivassiliou (The Cerebellum, 2025)
Speech problems are an early feature of Multiple System Atrophy (MSA). They can lead to social withdrawal and have significant impact on people’s quality of life. There is a considerable lack of clinical trials and clinicians lack guidance on how best to support this population. This project aimed to establish the feasibility and acceptability of a novel treatment approach, ClearSpeechTogether, in patients with the cerebellar variant of MSA (MSA-C), and to pilot an RCT comparing this treatment to standard speech and language therapy (SLT) treatment (ST). We recruited 24 patients with clinically probable MSA-C and dysarthria who were randomised to either treatment arm. Full data were available for 9 participants for ST, and 11 for ClearSpeechTogether. Both interventions lasted 6 weeks, ST offered 1 h of individual therapy a week, ClearSpeechTogether provided four individual therapy sessions over two weeks, followed by four weeks of daily, patient led group practice. Assessment and intervention were provided online via videoconferencing software. Data collection focused on feasibility, acceptability and signal of efficacy. Recruitment, conversion and attrition rates were within or close to target, and neither participants nor clinicians highlighted any acceptability issues. Communication outcomes were mixed, with biggest gains made in communication confidence and participation across both groups. Rapid decline in overall health status appeared to have impacted results. Results were generally positive and support the implementation of larger follow up trials. The study also demonstrated that people with MSA-C can benefit from speech therapy even at more severe stages of their disease progression.